Implementasi Nilai-Nilai Bhinneka Tunggal Ika Pada PemudaDi Masyarakat (Studi Kasus Di Kelurahan Sudiroprajan Kecamatan Jebres Kota Surakarta) - Andani, Oktaria; , Agus Prasetyo, S.Pd, M.Pd (2017)
This study aims to describe the implementation of the values of Unity in Diversity on youth in the Village community Sudiroprajan Jebres District of Surakarta include lementation, obstacles encountered, and the solutions provided. This research was qualitative, with a single case study strategy. Data collection techniques in this study were interviews, observation, and documentation. Test the validity of the data by triangulation triangulation of data sources and data collection techniques. Analysis of the data using interactive analysis techniques through data collection, data reduction, presentation and conclusion. This study shows some results. The first implementation of the values of unity in diversity in the youth in the community realized with respect realized by another person or group, accept differences of opinion another person or group; respect religious differences of others; creating harmony; helping each other, as well as deliberation in addressing the issue. Second, obstacles encountered when implementing the values of national unity which the youth in the meeting considers his opinion better than other people's opinions, youths do not accept dissent other members, youth portion has a fanatical attitude towards their religion, youth does not enthusiastically followed the activities that is in the community, youth preoccupied with the activities of the personal and the young man can not control their emotions when encountering differences in deliberation, the village must give strict sanctions for youth or residents who indicated to the violence that undermine harmony in Sub Sudiroprajan, every family needs to give attention or advice for children (youth) to participate in communities related to mutual help, and youth need to continue training for speaking in public, so as to give positive suggestions in overcoming the problems in society.